2004
DOI: 10.1590/s1413-86702004000200005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rapid diagnostic test OptiMAL for diagnosis of malaria due to Plasmodium vivax

Abstract: OBJECTIVE: To determine the sensitivity and specificity of the rapid diagnostic test OptiMAL® for diagnosis of Plasmodium vivax malaria. MATERIAL AND METHODS: We included all the patients who sought medical attention in the San Martin Pangoa Hospital, Junin, an area endemic for vivax malaria in Peru, between October and December 1998, who had fever during the previous 72 hours and who were older than 12 months. The gold standard for diagnosis was thick blood film microscopy. We determined the parasitemia rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…HRP2-based RDTs such as Parascreen™ have also been evaluated in various studies in South American countries [25-28]. The sensitivity and specificity for P. falciparum and P. vivax infections observed in this study were better than those reported with AMRAD fast test ICT P.f/P v in Peru [6], and similar to those obtained with Binax NOW™ fast test ICT P.f/P.v in Colombia, but lower than those observed with NOW-Malaria-ICT RDT in an evaluation study in Colombia [18] and in various other studies of OptiMAL IT [6,10,11,13,26]. …”
Section: Discussionsupporting
confidence: 83%
“…HRP2-based RDTs such as Parascreen™ have also been evaluated in various studies in South American countries [25-28]. The sensitivity and specificity for P. falciparum and P. vivax infections observed in this study were better than those reported with AMRAD fast test ICT P.f/P v in Peru [6], and similar to those obtained with Binax NOW™ fast test ICT P.f/P.v in Colombia, but lower than those observed with NOW-Malaria-ICT RDT in an evaluation study in Colombia [18] and in various other studies of OptiMAL IT [6,10,11,13,26]. …”
Section: Discussionsupporting
confidence: 83%
“…Optimal was evaluated positively by most researchers but not all: in Latin America, sensitivities for P. falciparum averaged 82% (range 42-100%) and for P. vivax 88% (65-100), including studies from Colombia, [15][16][17] Honduras, 4,18 Mexico, 19 Peru, 20 and Brazil; 21 in Asia it showed about 87% (79-94) sensitivity for P. falciparum and 80% (65-95) for P. vivax (Afghanistan, 22 Thailand, 23 Pakistan, 24 Kuwait 8 ). The NOW test and its predecessor ICT Pf/Pv were reported to be very sensitive for P. falciparum, about 96% (range 89-100) and a bit lower but acceptably sensitive for non-P. falciparum infections, about 87% (range 75-100, Colombia [Mendoza and others, unpublished data], Indonesia, 5 Thailand 25,26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lower specificity of PfHRP2‐detecting RDTs can partly be explained by the slow clearance of PfHRP2: in patients with recently treated or self‐cleared infections PfHRP2 may persist in the blood for several weeks and still be present during a new episode of fever. For P. vivax diagnosis, reported sensitivities for pan‐pLDH, Pv‐pLDH and aldolase‐detecting RDTs are, respectively, 76.1–100.0% , 76.9–100.0% and 80.0–81.4% . A prospective field study in Peru, comparing side‐to‐side 11 RDT products, revealed high sensitivity (>99.0%) for 9/11 products with no difference between pan‐pLDH vs. Pv‐pLDH detection .…”
Section: What Are the Diagnostic Characteristics Of Malaria Rdts In Tmentioning
confidence: 99%